Measurement of pH in Acetic Acid-Sodium Acetate Buffer Solutions - Shiv P. Mishra; R. P. Singh (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
A buffer solution refers to a system that has the property of being able to eliminate or diminish the influence of external conditions on a chemical system. In pH determination, various factors influence the pH of a buffer solution, including changes in temperature, ionic strength, hydrogen ion activity, dilution, and the addition of electrolyte salts. Acidic buffers have a pH of less than 7, where for neutral buffer solutions the pH is 7, and if any buffers have a pH of more than 7, it is known as basic buffers, respectively. In this study, the preparation of acetic acid-sodium acetate buffer solutions was reported, and its pH was determined by using a pH meter at about 25°C. In preparation of buffer solutions, firstly, 1.5 ml of glacial acetic acid was taken into a 100 ml standard flask for making up 0.2M of acetic acid solution, and 0.64 g of sodium acetate was dissolved in 100 ml of distilled water. Then, 36.2 ml of prepared solution of sodium acetate was taken into a 100 ml standard flask and 14.8 ml of prepared acetic acid was added to make its volume 100 ml by using distilled water, making it a buffer. In measuring the pH of prepared buffer solutions, a calibrated digital pen pH meter was used for quick resolution of readings with accuracy. The pH of acetic acid-acetate buffer solutions was gradually raised by adding a small quantity of 5N NaOH solution into the buffer sample, and the adjusted pH was adjusted to 4.7. By meticulously outlining the preparation process and employing a calibrated pH meter for precise pH determination, this study enhances the understanding of buffer systems’ behaviour when subjected to pH changes. Such insights are crucial for maintaining stable conditions in biochemical experiments and industrial processes, where pH control is vital for optimal performance and reaction outcomes.